Half-kilowatt high-energy third-harmonic conversion to 50 J @ 10 Hz at 343 nm - Jan Pilar; Martin Divoky; Jonathan Phillips; Martin Hanus; Petr Navratil; Ondrej Denk; Patricie Severova; Tomas Paliesek; Danielle Clarke; Martin Smrz; Thomas Butcher; Chris Edwards; et al. (High Power Laser Science and Engineering)
We present results of frequency tripling experiments performed at the Hilase facility on a cryogenically gas cooled multi-slab ytterbium-doped yttrium aluminum garnet laser system, Bivoj/DiPOLE. The laser produces high-energy ns pulses at 10 Hz repetition rate, which are frequency doubled using a type-I phase-matched lithium triborate (LBO) crystal and consequently frequency summed using a type-II phase-matched LBO crystal. We demonstrated a stable frequency conversion to 343 nm at 50 J energy and 10 Hz repetition rate with conversion efficiency of 53%.